Role of HCA2 in Regulating Intestinal Homeostasis and Suppressing Colon Carcinogenesis - Li, Zhuoyue; McCafferty, Kayleen J.; Judd, Robert L. (Frontiers in Immunology, 2021)
Hydroxycarboxylic acid receptor 2 (HCA2) is vital for sensing intermediates of metabolism, including β-hydroxybutyrate and butyrate. It also regulates profound anti-inflammatory effects in various tissues, indicating that HCA2 may serve as an essential therapeutic target for mediating inflammation-associated diseases. Butyrate and niacin, endogenous and exogenous ligands of HCA2, have been reported to play an essential role in maintaining intestinal homeostasis. HCA2, predominantly expressed in diverse immune cells, is also present in intestinal epithelial cells (IECs), where it regulates the intricate communication network between diet, microbiota, and immune cells. This review summarizes the physiological role of HCA2 in intestinal homeostasis and its pathological role in intestinal inflammation and cancer.